Antecedent and Consequences of Customer Engagement in Social Media Content: A Study Of Beauty Product Marketplace Marketing Activities in Instagram - Indira Pradipta; Gita Gayatri (JRB-Jurnal Riset Bisnis, 2023)
Instagram is a space for its users to engage with each other or the brand pages in it. This study investigates the effect of three customer engagement antecedents on the final outcome, namely loyalty. From this engagement relationship will produce an emotional bond to the brand generated by the customer so that it leads to a level of customer loyalty. This study aims to explore the relationship between engagement behavior on a giveaway content posted by a brand on Instagram and identify if there is a relationship between customer engagement and brand loyalty. This study uses purposive sampling from 250 Instagram users in Indonesia who followed two brand accounts on Instagram. SEM-PLS was used to see the relationship between variables. The findings imply that involvement, customer participation, and commitment have a positive effect toward customer engagement. Also, the antecedent of customer engagement has a significant effect on generating brand loyalty. The results provide a better understanding of digital marketing strategy by examining the influence of customer engagement toward brand loyalty by the giveaway content shared on social media.